Extracorporeal Membrane Oxygenation—First Strategy for Acute Life-Threatening Pulmonary Embolism - Liu, Zhenjie; Chen, Jinyi; Xu, Xin; Lan, Fen; He, Minzhi; Shao, Changming; Xu, Yongshan; Han, Pan; Chen, Yibing; Zhu, Yongbin; Huang, Man (Frontiers in Cardiovascular Medicine, 2022)
Background: Both venoarterial extracorporeal membrane oxygenation (VA-ECMO) and percutaneous mechanical thrombectomy (PMT) are increasingly used to treat acute life-threatening pulmonary embolism (PE). However, there are little data regarding their effectiveness. This study aimed to present the short-term outcomes after managing nine patients with acute life-threatening massive or submassive PE by VA-ECMO with or without complemented PMT and propose a preliminary treatment algorithm. Methods: This study was a single-center retrospective review of a prospectively maintained registry. It included nine consecutive patients with massive or submassive pulmonary embolism who underwent VA-ECMO for initial hemodynamic stabilization, with or without PMT, from August 2018 to November 2021. Results: Mean patient age was 54.7 years. Four of nine patients (44.4%) required cardiopulmonary resuscitation before or during VA-ECMO cannulation. All cannulations (100%) were successfully performed percutaneously. Overall survival was 88.9% (8 of 9 patients). One patient died from a hemorrhagic stroke. Of the survivors, the median ECMO duration was 8 days in patients treated with ECMO alone and 4 days in those treated with EMCO and PMT. Five of nine patients (55.6%) required concomitant PMT to address persistent right heart dysfunction, with the remaining survivors (44.4%) receiving VA-ECMO and anticoagulation alone. For survivors receiving VA-ECMO plus PMT, median hospital lengths of stay were 7 and 13 days, respectively. Conclusions: An ECMO-first strategy complemented with PMT can be performed effectively and safely for acute life-threatening massive or submassive PE. VA-ECMO is feasible for initial stabilization, serving as a bridge to therapy primarily in inoperable patients with massive PE. Further evaluation in a larger cohort of patients is warranted to assess whether VA-ECMO plus PMT may offer an alternative or complementary therapy to thrombolysis or surgical thrombectomy.